The Development of a Project-Based Learning Model in Islamic Education to Enhance Students’ Creativity - Nurjannah, Indah; Jannah, Eni Miftahul; Syafinka, Nabila; Setiawan, Hasrian Rudi; Nabilah, Wina (Yayasan Rahmat Islamiyah, 2025)
This study aims to develop a Project-Based Learning (PjBL) model in Islamic Education as an effort to enhance students’ creativity. The research employed a Research and Development (RD) approach by adapting the Borg Gall model, which includes needs analysis, model design, development, limited trial, revision, and wider implementation. The findings indicate that the developed PjBL model is aligned with the characteristics of Islamic Education learning, fosters active student engagement, and provides greater opportunities for creativity through real-life projects relevant to students’ daily experiences. Therefore, the development of a PjBL model in Islamic Education can serve as a strategic innovation to improve both learning quality and students’ creativity.